Tissue plasminogen activator does not increase neuronal damage in rat models of global and focal ischemia. - Klein, G; Li, H; Sun, P; Buchan, A (1999)
BACKGROUND: Intravenous tissue plasminogen activator (tPA) is the only approved treatment for acute ischemic stroke. Recent results from both in vitro and in vivo animal model experiments suggest the possibility that tPA is neurotoxic. METHODS: The authors evaluated the putative neurotoxicity of tPA in both global and focal animal models of ischemic stroke. Global ischemia was induced in male Wistar rats using a modified four-vessel occlusion technique, with percentage neuronal injury assessed at 7 days through necrotic and normal cell count in the CA1 region. Transient focal ischemia was induced in male spontaneously hypertensive rats subjected to middle cerebral artery clipping, with measurement of cortical infarct volume at 24 hours. tPA was administered in 1, 5, or 10 mg/kg doses given intravenously as a 10% bolus, 90% over the following hour, analogous to current human treatment protocols. RESULTS: In the global model, percent hippocampal injury was 60%+/-23%, 66%+/-26%, 55%+/-26%, and 52%+/-12% in the saline control, 1, 5, and 10 mg/kg tPA groups, respectively. In the focal model, after 120 minutes of ischemia, the control infarct size was 151+/-39 mm3, and for the group given 10 mg/kg of tPA, it was 158+/-28 mm3. CONCLUSIONS: Despite sublethal insults, with moderate injury induced by ischemia, there was no evidence that increasing doses of tPA exacerbated ischemic injury.